Implantação e estudo da viabilidade de nova rota de preparação de elementos ativos vítreos para microssensores do estado sólido - Neme, Maíra Dombroski (Universidade Federal de São Carlos, 2023)
The pH meter is currently one of the most commonly used probing devices, employed daily in industry, scientific research, and medicine. The search for new sensor materials is of great technological interest. In this work, we produced an ionic-conducting glass from the system Li2O-Y2O3-SiO2 using the Aerodynamic Levitation technique and later developed an all-solid-state pH sensor. An arrhenian tension response to change in pH was found, with a 43mV/pH coefficient. To better understand this characteristic, we simulated the Li2O-SiO2 system using Molecular Dynamics, which has extensive literature both in molecular dynamics and experiments, and compared its dynamic and structural properties with those of the Li2O-Y2O3-SiO2 glass. The diffusion coefficient of the latter was found to be two times larger than that of the former. It was also observed that the structural properties are very similar, except for the coordination numbers of the Li-O and Si-Si pairs, possibly indicating a less polymerized structure and higher lithium ion mobility.
Implementation and study of viability of a new route to prepare active vitreous elements for all-solid-state microssensors
Keywords: Microssensor do estado sólido; Sensor all-solid-state; pH; Levitação aerodinâmica; Dinâmica molecular; Aquecimento a laser; Vidro; Eletrodo; Condutor iônico; All-solid-state sensor; Aerodynamic levitation; Molecular dynamics; Laser heating; Glass; Probe; Ionic conductor; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA